Analisis Kesalahan Siswa dalam Menyelesaikan Soal Lingkaran di Kelas VIII SMP Negeri 1 Amandraya - Zebua, Viktor; Zega, Yulisman (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by the lack of student errors in working on problems on circle material. Student errors are one of the student errors in working on problems in mathematics learning such as conceptual errors, principal errors, and operational errors. With the aim of knowing the mistakes that students often make in working on math problems and one of the factors of student errors, namely students not understanding the intent of the questions, students cannot apply the formulas and steps in working on these questions. This study aims to find out students' mistakes in working on mathematical math test questions in class VIII SMP Negeri 1 Amandraya. This type of research is descriptive research with a qualitative approach. This research was conducted in class VIII SMP Negeri 1 Amandraya with a total of 35 students of research information. Data collection techniques through written tests, interviews and documentation. Based on the results of the research, it showed that students made mistakes in the work on the math test questions and there were still many students who still did not know how to work on the math test questions. This research has limitations, namely the small number of students, so the types of errors made by students are not very diverse